2015
DOI: 10.1097/inf.0000000000000774
|View full text |Cite
|
Sign up to set email alerts
|

Brain Imaging and Neurodevelopment in HIV-uninfected Thai Children Born to HIV-infected Mothers

Abstract: Background Perinatal use of combination antiretroviral therapy dramatically reduces vertical (mother-to-child) transmission of HIV, but has led to a growing population of children with perinatal HIV-exposure but uninfected (HEU). HIV can cause neurological injury among children born with infection, but the neuroanatomical and developmental effects in HEU children are poorly understood. Methods We used structural magnetic resonance imaging (MRI) with diffusion tensor imaging (DTI) to compare brain anatomy bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 52 publications
(55 reference statements)
3
24
0
Order By: Relevance
“…Abnormal Dubowitz neurobehavioral scores were positively correlated with FA in the left uncinate fasciculus and negatively correlated with diffusivity in the right inferior cerebellar peduncle and bilateral hippocampal cingulum in HEU infants . The third study using DTI in age‐matched HEU and HUU children did not detect group differences in intelligence quotient (IQ) scores, brain volume, or DTI metrics, after controlling for sociodemographic factors . This study found that DTI measures were significantly associated with full scale and performance IQ scores, showing positive associations with FA and negative associations with diffusivity metrics.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Abnormal Dubowitz neurobehavioral scores were positively correlated with FA in the left uncinate fasciculus and negatively correlated with diffusivity in the right inferior cerebellar peduncle and bilateral hippocampal cingulum in HEU infants . The third study using DTI in age‐matched HEU and HUU children did not detect group differences in intelligence quotient (IQ) scores, brain volume, or DTI metrics, after controlling for sociodemographic factors . This study found that DTI measures were significantly associated with full scale and performance IQ scores, showing positive associations with FA and negative associations with diffusivity metrics.…”
Section: Resultsmentioning
confidence: 69%
“…Post‐screening, 255 full‐text articles were critically reviewed, and 25 met inclusion criteria for the systematic review (Figure ). Five articles included human subjects and studied brain size, structure and function . The remaining 20 articles were preclinical studies using animal models mostly focused on behavioural assessments (see Tables and for study characteristics and summary of outcomes).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A key goal in scanning these cohorts is to establish growth rate “norms” based on as much statistical data as possible. Despite the large effect sizes for structural brain differences in elderly cohorts with HIV [37], brain differences between HIV+ and HIV- children have been more difficult to identify [38]. …”
Section: Introductionmentioning
confidence: 99%